2011
DOI: 10.1097/tp.0b013e31822d4de1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Urinary CXCL10 As a Marker of Borderline, Subclinical, and Clinical Tubulitis

Abstract: This study validates urinary CXCL10 as a noninvasive, sensitive, and specific marker for tubulitis in an independent cohort. The straightforward urine processing is accessible to clinical laboratories. We propose that CXCL10 may be useful as a supplementary noninvasive screening test for tubulitis in renal transplant patients, with a level more than 1.97 ng CXCL10/mmol Cr being a threshold to consider biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 32 publications
10
67
4
2
Order By: Relevance
“…For example, in the extensive analysis conducted by the Winnipeg group, the urine CXCL10 level was associated with tubulitis, a feature of TCMR. 4,10,11 In addition, in the recent CTOT-01 Study that validated urinary CXCL9 as a diagnostic biomarker of AR, only six biopsies showed evidence of ABMR. Urinary CXCL9 and CXCL10 levels have also been shown to be diagnostic of BK virus-associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the extensive analysis conducted by the Winnipeg group, the urine CXCL10 level was associated with tubulitis, a feature of TCMR. 4,10,11 In addition, in the recent CTOT-01 Study that validated urinary CXCL9 as a diagnostic biomarker of AR, only six biopsies showed evidence of ABMR. Urinary CXCL9 and CXCL10 levels have also been shown to be diagnostic of BK virus-associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Suthanthiran et al 2 recently showed that the urinary cell mRNA profile can serve as a diagnostic and prognostic biomarker of TCMR. Protein markers have also been assessed for their ability to predict both clinical [3][4][5][6][7] and subclinical TCMR. 4,[8][9][10][11] C-X-C motif chemokine 9 (CXCL9) and CXCL10 are IFNg-dependent, C-X-C motif chemokine receptor 3-binding chemokines that are secreted by infiltrating inflammatory cells and renal tubular and mesangial cells.…”
mentioning
confidence: 99%
“…rejection and polyomavirus-BK nephropathy) (12)(13)(14). Furthermore, it correlated with the extent of subclinical tubulitis in two independent patient cohorts (15,16).…”
Section: Introductionmentioning
confidence: 96%
“…A key limitation of these studies is that they included selected patient groups (12)(13)(14)(15)(16). As a consequence, the frequency of the investigated pathologies did not reflect real life, and thus cut-off determination of urinary CXCL10 for prediction of clinical/subclinical allograft inflammation and calculation of its diagnostic characteristics is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…3) Šlapimo CXCL10 kaip ankstyvą tubulito žymenį nagrinėjo Ho su bendraautoriais [11]. Tyrėjai lygino šlapimo CXCL10 koncentraciją suskirstę pacientus į šešias grupes pagal inksto biopsijos rezultatus: norma, intersticinė fibrozė/kanalėlių atrofija (IFKA), IFKA bei paribinis tubulitas, paribinis tubulitas, subklinikinis tubulitas ir klinikinis tubulitas.…”
Section: Chemokinai Ir Transplantato Atmetimasunclassified